2005
DOI: 10.1002/jgt.20124
|View full text |Cite
|
Sign up to set email alerts
|

(d,1)‐total labeling of graphs with a given maximum average degree

Abstract: The (d,1)-total number T d (G) of a graph G is the width of the smallest range of integers that suffices to label the vertices and the edges of G so that no two adjacent vertices have the same color, no two incident edges have the same color, and the distance between the color of a vertex and its incident edges is at least d. In this paper, we prove that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 9 publications
(7 reference statements)
0
15
0
1
Order By: Relevance
“…In a companion paper, we will give the relationship between the (d, 1)-total labelling of a graph G and its maximum average degree [12].…”
Section: Conjecturementioning
confidence: 99%
“…In a companion paper, we will give the relationship between the (d, 1)-total labelling of a graph G and its maximum average degree [12].…”
Section: Conjecturementioning
confidence: 99%
“…As for the (2, 1)-total labeling number of outerplanar graphs is known to be at most ∆ + 2, which is tight, i.e., there exists an outerplanar graph whose (2, 1)-total labeling number is ∆ + 2 [36,37]. Also, there are many related works about bounds on λ T p,1 (G) [17,38,52,56]. From the algorithmic point of view, Havet and Thomassé [41] showed that for bipartite graphs, if (i) p ≥ ∆ or (ii) ∆ = 3 and p = 2, then the (p, 1)-total labeling problem is polynomially solvable and otherwise it is NP-hard.…”
Section: (P Q)-total Labelingmentioning
confidence: 99%
“…In Yu et al (2011), Yu et al proved that every planar graph with maximum degree ≥ 12 satisfies that + 1 ≤ λ T 2 ≤ + 2. The ( p, 1)-total labelling conjecture in general has been considered for some other classes such as planar graphs with high girth and high maximum degree (Bazzaro et al 2007) and graphs with a given maximum average degree (Montassier and Raspaud 2006). Particularly, Bazzaro, Montassier and Raspaud proved the following theorem for all planar graphs (Bazzaro et al 2007).…”
Section: Introductionmentioning
confidence: 96%